2020
DOI: 10.1002/marc.202000021
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Palladium‐Catalyzed Direct Arylation Polymerization of 2‐Bromothiophene Derivatives

Abstract: Conjugated polyelectrolytes have been utilized in applications including chemical/biosensing, [30][31][32] cell imaging, [33][34][35] and disease diagnosis/therapy. [36,37] Their synthesis comprises the preparation of organic-soluble conjugated polymers followed by post-functionalization. A typical post-functionalization reaction is the nucleophilic substitution of an alkyl-bromide with amines to afford ammonium salts, which render the resultant conjugated polyelectrolytes aqueous soluble. However, post-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Cross-coupling polymerization methods such as Stille, Suzuki, and direct arylation are better choices to ensure the synthesis of well-defined alternating copolymers. However, few of these coupling reactions are adapted for the synthesis of water-soluble materials. , Recently, some studies showed that the addition of water or the use of polar solvents is compatible with direct (hetero)­arylation polymerization (DHAP) reactions. For instance, the addition of water has shown to allow the synthesis of materials with good molecular weight even in the presence of air in the system . Biphasic conditions also permit to eliminate the use of anhydrous solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-coupling polymerization methods such as Stille, Suzuki, and direct arylation are better choices to ensure the synthesis of well-defined alternating copolymers. However, few of these coupling reactions are adapted for the synthesis of water-soluble materials. , Recently, some studies showed that the addition of water or the use of polar solvents is compatible with direct (hetero)­arylation polymerization (DHAP) reactions. For instance, the addition of water has shown to allow the synthesis of materials with good molecular weight even in the presence of air in the system . Biphasic conditions also permit to eliminate the use of anhydrous solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Further, favorable intermolecular interactionsmay be slowed down by the “melt-like” state in which the reaction is developing. Consequently, performing polymerization in bulk at a higher temperature than 150 °C in solution (in the presence of Lewis [ 122 ] or Bronsted [ 123 ] acids) or alternatively, based on its aqueous self-dispersibility, applying direct arylation in an aqueous medium [ 126 ] is expected to have better performance creating a polythiophene-g-OMeOx, and these ideas will be explored in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the development of efficient water-only polymerization conditions is still a work in progress [31,57]. As an example, Lin and colleagues [57] recently reported DHAP conditions enabling the polymerization of both cationic and anionic polymers by using water as the only solvent.…”
Section: Trends Trends In In Chemistry Chemistrymentioning
confidence: 99%